Gi‐DREADD activation decreases Epithelial Na+ channel activity in renal principal cells - Tarek Mohamed Abd El‐Aziz; Elena Mironova; James D. Stockand; Lucia A. Seale; Antonio G. Soares (Physiological Reports, 2025)
Abstract The activity of the Epithelial Na+ Channel (ENaC) in renal principal cells (PC) fine‐tunes sodium excretion and consequently affects blood pressure. G‐coupled receptors play an important role in regulating ENaC activity. We previously explored the role of Gq and Gs in regulating ENaC activity by using the designer receptors exclusively activated by designer drugs (DREADD) technology. We demonstrated that pharmacogenetic activation of Gq (Gq‐DREADD) exclusively in principal cells by Clozapine‐N‐oxide (CNO) reduced ENaC activity in renal tubules, promoting natriuresis that lowered elevated blood pressure in the DOCA‐salt model of hypertension. In addition, by investigating the Gs‐adenylyl cyclase‐cAMP signal transduction pathway, we exhibited that treatment of PC‐specific Gs‐DREADD mice with CNO rapidly and significantly decreased urinary Na+ excretion. In this study, we investigate the role of Gi‐DREADD in regulating ENaC activity. Our results showed that Gi‐DREADD, expressed exclusively in renal principal cells, activated by CNO reduced ENaC activity and significantly increased urinary Na+ excretion compared to CNO‐treated littermates. These findings provide for the first time that target activation of Gi signaling exclusively in PCs is sufficient to decrease ENaC activity and increase dependent urinary Na+ excretion in live animals.